O museu como um espaço de lazer, educação e linguagens: uma análise das práticas pedagógicas voltadas para o processo de formação de mediadores do grupo Miguilim, no Museu Casa Guimarães Rosa - Stephanie de Oliveira Souza (2023)
The school environment stands out as the main vehicle for cultural dissemination and the development of meaningful learning, allowing students deep self-knowledge and understanding of the world. However, museums emerge asfundamental spaces for civic education, going beyond aesthetic appreciation and acting as cultural interpretive centers that strengthen cultural democracy. In this context, the research focused on the Casa Guimarães Rosa Museum in Cordisburgo, MG, and its interconnection with the Miguilim Storytellers Group Project, which operates with the local basic education students. The study aimed to understand how the museum's pedagogical practices influence the formation of the project's mediators, as well as the perception of this place as an educational and leisure environment. The methodological approach included bibliographic research, observation, and semi-structured interviews with twenty participants, elucidating the impact of the museum's cultural and formative initiatives on the trajectory of young people and their experiences in the project. The theoretical framework includes studies on leisure, about museum and its potential for education and leisure, mediation, and cultural identity. The analysis of the results shows us that cultural mediation is essential for individuals to have more effective access to their cultural heritage and its meanings, which favors educational formation through the development of language and literacy, the constitution of cultural identity, and confirms their belonging to the territory and the community. The results also confirmed that the museum can serve as a space for leisure and sociability, reinforcing the individual's civic educational formation.